2014
DOI: 10.1186/s12934-014-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature cultivation of recombinant Pichia pastorisincreases endoplasmic reticulum stress and decreases production of human interleukin-10

Abstract: BackgroundThe yeast Pichia pastoris (P. pastoris) has become a popular ‘cell factory’ for producing heterologous proteins, but production widely varies among proteins. Cultivation temperature is frequently reported to significantly affect protein production; however, the underlying mechanisms of this effect remain unclear.ResultsA P. pastoris strain expressing recombinant human interleukin-10 (rhIL-10) under the control of the AOX1 promoter was used as the model in this study. This system shows high-yield rhIL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 47 publications
(49 reference statements)
2
43
0
3
Order By: Relevance
“…To further increase the yield of pGH, the optimal temperature, pH and culture time for expression of pGH protein in Pichia pastoris were investigated by single factor experiments. Previous findings showed that low temperature induction resulted in more conducive to the expression of heterologous proteins in Pichia pastoris [52,53]. In our study, the expression of pGH protein in Pichia pastoris was highest at 20 °C, pH 6.0, for 48 h, which mirrored the finding that mRNA is more stable at the low temperature [54].…”
Section: Discussionsupporting
confidence: 86%
“…To further increase the yield of pGH, the optimal temperature, pH and culture time for expression of pGH protein in Pichia pastoris were investigated by single factor experiments. Previous findings showed that low temperature induction resulted in more conducive to the expression of heterologous proteins in Pichia pastoris [52,53]. In our study, the expression of pGH protein in Pichia pastoris was highest at 20 °C, pH 6.0, for 48 h, which mirrored the finding that mRNA is more stable at the low temperature [54].…”
Section: Discussionsupporting
confidence: 86%
“…By reducing the induction temperature, we decrease the rate of protein synthesis, and give time for newly translated recombinant protein to fold properly. According to other literature examples, lowering induction temperature does not only lead to a higher expression, it can also lead to a more active protein [22] and an increase in cell viability [23,24]. Indeed, transcriptomic [25] and proteomic [26] analyses of Pichia pastoris recombinant protein expression at a lower temperature showed a strong decrease in folding stress, noticed by the decrease of chaperones and other folding-related proteins.…”
Section: Discussionmentioning
confidence: 93%
“…More precisely, the small variation in cell mass could therefore not be responsible for the observed increases in yield. Indeed, Zhong et al also observed that, during methanol induction, there was no statistical influence of a lower temperature on the growth curve of recombinant Pichia pastoris [23]. Although their experiment used an induction temperature of 20°C, it is remarkable that these results hold true for 16°C as well.…”
Section: Discussionmentioning
confidence: 98%
“…Er-phagy has two subtypes, these subtypes are macro-ER-phagy and micro-ER-phagy which does not use autophagic organelles and machinery [123]. ER-phagy which selectively seizes protein aggregates containing ER fragments and returns the ER to its normal size once folding stress subsides, is suggested to provide a survival advantage in response to ER stress [124]. ER-phagy occurs after extended times of starvation or ER stress [125].…”
Section: Er-phagymentioning
confidence: 99%